Alternative methods for control of reproduction in small ruminants: A focus on the needs of grazing industries. (1st January 2015) - Delgadillo, J. Alberto; Martin, Graeme B.
Abstract: Extensive grazing systems need simple, low-cost tools for managing reproduction that improve productivity while nurturing future markets. To develop such tools, we need to understand the biology of the grazing animals in their particular environments. Nutrition is the primary challenge because it is limited to grazing, but nutrition also offers opportunities for improving animal health and carbon emissions. Nutritional inputs must be coordinated with reproductive events. We use the term "focus feeding" (optimized management of nutrition, a concept that has much in common with "nutrient synchrony"). To coordinate nutritional inputs with reproductive events, we can control the timing of reproduction by restriction of male access to females and then add precision with the male effect and, ultimately, ultrasound for pregnancy detection and measurement of potential litter size. Maximum neonatal survival is an imperative, so management of the birth site should be a high priority. The power of genetics must underpin any management strategy, with breeding goals that take advantage of the strengths of indigenous genotypes and matching their performance to their environment.